2017
DOI: 10.1590/s1517-707620170002.0161
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Mechanical Properties of Borided Inconel 625 Superalloy

Abstract: The Ni-based superalloy Inconel 625 is extensively used owing to its high strength, excellent fabricability, good weldability and outstanding resistance to high temperature corrosion against aggressive environments. However, despite its unique properties and extensive use, its wear resistance is in some cases unsatisfactory. In this study, Inconel 625 was subjected to boriding treatments at different temperature and different durations. Microstructural characterization was made by conventional methods (scannin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 14 publications
0
16
0
Order By: Relevance
“…The elements Nb and C continue to consume, and the austenitic and Laves phase eutectic reaction takes place depending on the already formed austenitic matrix. [ 40 ] It can be seen from the result of the energy spectrum shown in Figure 15. The elements Mo and Nb gathered in the grain boundary, so in the local scope grain boundary, the composition of liquid with Inconel 625 original ingredients make a big difference, formed the composition is undercooling, accelerate the process of the coagulation equation L → L + γ → L + γ + Nbc + Laves → γ + Nbc + Laves , the schematic diagram is shown in Figure .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The elements Nb and C continue to consume, and the austenitic and Laves phase eutectic reaction takes place depending on the already formed austenitic matrix. [ 40 ] It can be seen from the result of the energy spectrum shown in Figure 15. The elements Mo and Nb gathered in the grain boundary, so in the local scope grain boundary, the composition of liquid with Inconel 625 original ingredients make a big difference, formed the composition is undercooling, accelerate the process of the coagulation equation L → L + γ → L + γ + Nbc + Laves → γ + Nbc + Laves , the schematic diagram is shown in Figure .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there are many studies of Inconel 625 alloy additive manufacture, including the plastic deformation behavior, dynamic recrystallization, microstructure investigation, parametric study, and mechanical model. [ 1–3,6,37,39,40,43,45–47,52–55 ] Hua et al [ 42 ] got the Inconel 625 super alloy sample, which is fabricated by DED, and treated by the hot compression tests. The plastic deformation behavior and dynamic recrystallization (DRX) phenomenon were investigated by them.…”
Section: Introductionmentioning
confidence: 99%
“…This type of defect is often observed in metal and alloys with FCC structures. Twins in Ni-200 alloy under investigation are confined inside the grains, in contrarily to annealing twins that are characterized by straight lines extending across the grain boundaries [11]. Ni-200 alloy has been reported to have a single phase and has a microstructure similar to that of austenitic stainless steel [12].…”
Section: Microstructure Investigationmentioning
confidence: 99%
“…The failure of a heat exchanger raises questions about the cause of failure, which one or more of four main causes; corrosion, mechanical, mechanical induced corrosion, or scale-mud-and algae-fouling [10]. The corrosion of heat exchangers has been reported to be in general corrosion form or many localized corrosion forms such as galvanic corrosion, pitting, intergranular corrosion, crevice corrosion, microbiologically influenced corrosion (MIC), erosion corrosion, stress corrosion cracking (SCC), hydrogen embrittlement, etc [11].…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the wear volume dropped more than 40 times due to alloying surface with boron [ 20 ]. In 2017, Gunen et al confirmed these results on Inconel 625 by obtaining improved wear resistance by boriding [ 21 ] and borotitanizing [ 22 ]. In 2019, Silva et al reported similar results for Inconel 718 [ 23 ] and Gheisari et al proved that boriding increases wear resistance of nickel alloys in elevated temperatures as well [ 24 ].…”
Section: Introductionmentioning
confidence: 95%